PENDIDIKAN KARAKTER BERBASIS IMAN DAN TAQWA TERHADAP PESERTA DIDIK (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Character education has become a plemic in various countrie. Views of the pros and cons coloring the character education discourse. Character education is an essential part of school work, but so farhas been lacking attention. Character education is defined as the deliberate us of all demision of school life to foster optimal character development. This means that to support the development of student character must involve all components in the school both from the aspect of curriculum content, the procces of instruction, the quality of relationships, the handling of discipline, implementation of co-curricular activities and ethos throughout the school environment. Islam is the teaching of Allah swt to manind through his messenger, from Adam as to the prophet Muhammad saw. In the generation of prophets Muhammad saw the teaching is in the Al-Qur’an. That is why Allah swt positioned the Al-Qur’an as a guide for mankid and the prophet Muhammad saw in the position of Allah swt as an ideal model because he is considered by Allah swt as a person who has a perfect character( insan kamil).